2010
DOI: 10.1139/f10-001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal reaction norms in sperm performance of Atlantic cod (Gadus morhua)

Abstract: Phenotypic plasticity occurs when a genotype produces variable phenotypes under different environments; the shapes of such responses are known as norms of reaction. The genetic scale at which reaction norms can be determined is restricted by the experimental unit that can be exposed to variable environments. This has limited their description beyond the family level in higher organisms, thus hindering our understanding of differences in plasticity at the scale of the individual. Using a three-year common-garde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 55 publications
0
54
0
Order By: Relevance
“…This behaviour probably limited males to positions near the seafloor, which was almost entirely within the warmer bottom layer at the start of the study. The effects of elevated temperature on male gamete quality in cod are not well understood (Purchase et al 2010), but may not be as adverse as those observed for females (van der Meeren & Ivannikov 2006). Even so, on Day 20 there was a pronounced downwelling of cooler surface water (Fig.…”
Section: Environmental Regulators: Temperature Light and Windmentioning
confidence: 99%
“…This behaviour probably limited males to positions near the seafloor, which was almost entirely within the warmer bottom layer at the start of the study. The effects of elevated temperature on male gamete quality in cod are not well understood (Purchase et al 2010), but may not be as adverse as those observed for females (van der Meeren & Ivannikov 2006). Even so, on Day 20 there was a pronounced downwelling of cooler surface water (Fig.…”
Section: Environmental Regulators: Temperature Light and Windmentioning
confidence: 99%
“…Pagination not final (cite DOI) / Pagination provisoire (citer le DOI) Purchase et al (2010) documented no family-level differences in reaction norms in their examination of sperm performance in Atlantic cod (Gadus morhua). However, they did detect differences in reaction norms among individuals, whereby the sperm essentially imitated clonal replicates.…”
Section: Figmentioning
confidence: 99%
“…This phenomenon is exemplified in work by Beacham and Murray (1985) on chum salmon (Oncorhynchus kisutch). Although Purchase et al (2010) investigated whether thermal extremes revealed cryptic variation in cod sperm performance, their test was inconclusive because individual variability in sperm swimming velocity (Fig. 3) and sperm wobble was greatest at the lower temperatures (those most similar to temperatures likely encountered in the wild) and minimal at the highest temperature.…”
Section: Treatment Designmentioning
confidence: 99%
See 1 more Smart Citation
“…As cod sperm are greatly affected by temperature (Purchase et al 2010), the percentage of motile sperm and swimming characteristics of motile cells were analyzed at a controlled 9°C within 10 h of collection following the protocol described by Beirão et al (2014). The seawater (31.7 psu and 964 mOsm kg −1 ) was filtered and UV sterilized.…”
Section: Motility Analysesmentioning
confidence: 99%